KELEMAHAN DAN KELEBIHAN PEMBERHENTIAN PRESIDEN MENURUT KONTITUSI - HABIBI, HABIBI (Prodi Hukum Agama Hindu Jurusan Dharma Sastra STAHN Gde Pudja Mataram, 2018)
This research purposed to examing and analiyzing what are weaknes and strength of impeacgment presiden according to UUD republic Indonesia 1945 about UUD beore amandemen. Methode of research based on the kind of normative law. The approach thad use to this research are :statute approach, historitical approach, comparative approach.The strenght of impeachment presiden according to UUD republic of indonesia 1945 is existance arrangement that eleares so that there is lawa of assuarance, because impeachment presiden have to courf of constitution isntitute mean while the weakness in UUD republic of indonesia 1945 in impeachment presiden consit of arbiraines of unliteral about meaning in setion 7A concerning the reason stopage of presiden and also issue that appear how low sternght that made by court of constitution so thar presiden or vie presiden can be responsible of criminal conduct when evidence to do law of uwlatin that accussed by DPR. Possiblity can be money politic to process impeachment at DPR or MPR that done by presiden or vice presiden.